2012
DOI: 10.1007/s00210-012-0821-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo pharmacological profile of the selective β3-adrenoceptor agonist mirabegron in rats

Abstract: To investigate the pharmacological properties of mirabegron in in vitro and in vivo, the effects on cAMP accumulation in Chinese hamster ovary (CHO) cells expressing rat β-adrenoceptors, the relaxant activity in isolated rat bladder smooth muscle, and the voiding effects in cerebral infarcted rats were evaluated. Mirabegron increased cAMP accumulation with EC(50) value and intrinsic activity of 19 nmol/L and 1.0, respectively, in CHO cells expressing rat β(3)-adrenoceptors. The EC(50) values and the intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
6
20
0
Order By: Relevance
“…In human embryonic kidney (HEK) cells stably transfected with human β 3 -adrenoceptors at a density of 121-fmol/mg protein, mirabegron and isoprenaline exhibited apparent affinities of 55 nM and 34 μM, respectively, in competition radioligand binding studies, and these affinities were not substantially altered in HEK cells transfected with several naturally occurring gene variants of the receptor ). In cyclic AMP accumulation experiments in these HEK cells, mirabegron and isoprenaline exhibited EC 50 values of 0.93 and 11.2 nM, respectively, and the efficacy of mirabegron relative to isoprenaline was 0.85, which is in good agreement with the findings in CHO cells (Hatanaka et al 2013b;Takasu et al 2007). The potency and efficacy of mirabegron also was not affected by genotype in these experiments.…”
Section: Biochemical and Cellular Studiessupporting
confidence: 87%
See 3 more Smart Citations
“…In human embryonic kidney (HEK) cells stably transfected with human β 3 -adrenoceptors at a density of 121-fmol/mg protein, mirabegron and isoprenaline exhibited apparent affinities of 55 nM and 34 μM, respectively, in competition radioligand binding studies, and these affinities were not substantially altered in HEK cells transfected with several naturally occurring gene variants of the receptor ). In cyclic AMP accumulation experiments in these HEK cells, mirabegron and isoprenaline exhibited EC 50 values of 0.93 and 11.2 nM, respectively, and the efficacy of mirabegron relative to isoprenaline was 0.85, which is in good agreement with the findings in CHO cells (Hatanaka et al 2013b;Takasu et al 2007). The potency and efficacy of mirabegron also was not affected by genotype in these experiments.…”
Section: Biochemical and Cellular Studiessupporting
confidence: 87%
“…Two studies on CHO cells transfected with human β-adrenoceptor subtypes were reported with rather similar results. Thus, mirabegron stimulated cyclic AMP accumulation via β 3 -adrenoceptors with EC 50 values of 22 nM (Takasu et al 2007) and 1.5 nM (Hatanaka et al 2013b), its efficacy relative to isoprenaline was 0.8 in both studies; in contrast, efficacy at human β 1 -and β 2 -adrenoceptors was only 0.1-0.2 in both studies, which did not allow quantification of potency. In human embryonic kidney (HEK) cells stably transfected with human β 3 -adrenoceptors at a density of 121-fmol/mg protein, mirabegron and isoprenaline exhibited apparent affinities of 55 nM and 34 μM, respectively, in competition radioligand binding studies, and these affinities were not substantially altered in HEK cells transfected with several naturally occurring gene variants of the receptor ).…”
Section: Biochemical and Cellular Studiesmentioning
confidence: 87%
See 2 more Smart Citations
“…In organ-bath studies, mirabegron relaxed normal human urinary bladder strips [19], increased intracellular cAMP levels and activated cAMP-dependent protein kinase A [20]. This resulted in the activation and phosphorylation of myosin light-chain kinase, mediating inhibition of the Ca 2+ -calmodulin dependent interaction with actin, and a decrease in intracellular cytoplasmic Ca 2+ [21].…”
Section: Introductionmentioning
confidence: 99%